ENHANCING STUDENT ENGAGEMENT IN ONLINE LEARNING ENVIRONMENTS: STRATEGIES AND BEST PRACTICES - Sajad Ahmad Malik (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Online learning has become an integral component of contemporary education, offering flexibility and accessibility. However, ensuring active student engagement in virtual classrooms remains a persistent challenge. This work explores strategies and best practices to enhance student engagement in online learning environments. A comprehensive literature review synthesizes existing knowledge on factors influencing engagement, theories guiding online learning, and the impact of technology. The study employs a mixed-methods approach, combining surveys and interviews to gather insights from a diverse sample of online learners. Findings reveal key strategies, such as interactive course design, timely feedback, and fostering a sense of community, that significantly contribute to increased engagement. The discussion interprets these results in light of current literature, highlighting practical implications for educators and administrators. As online education continues to evolve, this research offers valuable insights into cultivating a vibrant and participatory virtual learning experience. The conclusion emphasizes the importance of adopting these strategies to optimize student engagement and underscores the need for ongoing research in this dynamic educational landscape.